Thermodynamic Parameters of Lead Sulfide Chrystals in the Cubic Phase - Parashchuk, T.; Zagorodnyuk, A.; Nykyruy, L.; Volochanska, B.; Mazur Т. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
Geometric and thermodynamic parameters of cubic PbS crystals were obtained using the computer calculations of the thermodynamic parameters within density functional theory method DFT. Cluster models for the calculation based on the analysis of the crystal and electronic structure. Temperature dependence of energy ΔE and enthalpy ΔH, Gibbs free energy ΔG, heat capacity at constant pressure CP and constant volume CV, entropy ΔS were determined on the basis of ab initio calculations of the crystal structure of molecular clusters. Analytical expressions of temperature dependences of thermodynamic parameters which were approximated with quantum-chemical calculation points have been presented. Experimental results compared with theoretically calculated data.